2013
DOI: 10.1590/s0100-06832013000300028
|View full text |Cite
|
Sign up to set email alerts
|

Forms and accumulation of copper and zinc in a sandy typic hapludalf soil after long-term application of pig slurry and deep litter

Abstract: SUMMARYSuccessive applications of pig slurry and pig deep litter may lead to an accumulation of copper (Cu) and zinc (Zn) fractions in the soil profile. The objective of this study was to evaluate the Cu and Zn forms and accumulation in a Sandy Typic Hapludalf soil after long-term application of pig slurry and deep litter. In March 2010, eight years after initiating an experiment in Braço do Norte, Santa Catarina (SC), Brazil, on a Sandy Typic Hapludalf soil, soil samples were collected from the 0-2.5, 2.5-5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
2
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
2
19
2
6
Order By: Relevance
“…On average, these two operations were conducted every 2 or 3 yr and only affected depths of up to 0.15 m. These results correspond with those obtained by Tiecher et al (2013), who observed greater soluble, exchangeable, and available Cu and Zn concentrations in the surface layer (0.00-0.10 m) of the Hapludalf soils with annual applications of 90-180 m 3 ha -1 of pig slurry in southern Brazil. The Cu sol and Zn sol fractions, which represent the water-soluble and readily bioavailable fractions of Cu and Zn, were most abundant in the soils in the 14 yr, 18 yr, 25 yr, 28 yr, and 30 yr areas at depths of less than 0.30-0.40 m, most likely due to the longer time and higher frequency of pig slurry application in these areas.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On average, these two operations were conducted every 2 or 3 yr and only affected depths of up to 0.15 m. These results correspond with those obtained by Tiecher et al (2013), who observed greater soluble, exchangeable, and available Cu and Zn concentrations in the surface layer (0.00-0.10 m) of the Hapludalf soils with annual applications of 90-180 m 3 ha -1 of pig slurry in southern Brazil. The Cu sol and Zn sol fractions, which represent the water-soluble and readily bioavailable fractions of Cu and Zn, were most abundant in the soils in the 14 yr, 18 yr, 25 yr, 28 yr, and 30 yr areas at depths of less than 0.30-0.40 m, most likely due to the longer time and higher frequency of pig slurry application in these areas.…”
Section: Discussionsupporting
confidence: 87%
“…Using this technique, especially in experiments using soils with increasing pig slurry applications, one can observe that Cu and Zn accumulate in the organic and mineral soil fractions, with Zn preferentially adsorbing to surface functional groups in the mineral soil fraction (L'Herroux et al 1997;Girotto et al 2010). However, studies of the Cu and Zn fractions in soils treated with slurry, including pig slurry, have mainly been performed in experimental areas Guan et al 2011;Tiecher et al 2013). Few studies have been conducted on the accumulation of Cu and Zn in different soil fractions on farms in microwatersheds, where the soils mainly have sandy textures and a long history of pig slurry application.…”
mentioning
confidence: 99%
“…The increases in Cu contents of 3.2, 5.5 and 11.7 times and in Zn contents of 2.8, 4.5 and 9.8 times with the use of 20, 40 and 80 m 3 ha -1 of PS, respectively, are pronounced, as discussed in detail by Girotto et al (2010). Tiecher et al (2013) also reported an increase in the Cu and Zn contents in soil subjected to PS application, which may lead to toxicity to plants, but also to the transfer of more soluble Cu and Zn forms in the runoff solution on the soil surface. It is also worth mentioning that according to the CONAMA resolution No.…”
Section: Resultsmentioning
confidence: 86%
“…Com isso, há melhoria no ambiente químico do solo para o crescimento de raízes, por causa do aumento da saturação por bases e da redução da saturação por Al (Lourenzi et al, 2011;Brunetto et al, 2012). No entanto, também pode ocorrer o aumento dos teores de metais pesados no solo, como Cu e Zn Mattias et al, 2010;Basso et al, 2012;Popovic & Jensen, 2012;Tiecher et al, 2013), remanescentes de rações consumidas pelos suínos. Isso porque em torno de 90% do Cu e do Zn ingeridos pelos suínos por meio dos suplementos minerais são excretados nas fezes e na urina, estando presentes nos dejetos (Aldrich et al, 2002;Nicholson et al, 2003).…”
Section: Introductionunclassified